Financial Literacy, Financial Technology, and Risk Tolerance on Interest in Investing in Shares (Institut Agama Islam Negeri Kudus, 2024)
AbstractThis research aims to find out whether financial literacy, financial technology, and risk tolerance influence investment interest in the Islamic capital market. This quantitative research uses field research with primary data obtained from distributing questionnaires. The sampling technique used is probability sampling. The respondents in this study were 85 respondents from the total student population of FEBI IAIN Kudus and were processed using the SmartPLS 4 program. The results of this research are that the financial literacy variable has a significant influence on students' investment interest with a statistical t-value greater than the t-table (2.98 > 1.96) with p-values (0.003 < 0.05). The financial technology variable has a significant influence on investment decisions with a t-statistical value greater than the t-table (2.98 > 1.96) with a p-value of (0.003 < 0.05). Meanwhile, the risk tolerance variable does not have a significant influence on investment decisions with the t-statistic being smaller than the t-table (0.901 < 1.96) with a p-value of (0.368 > 0.05).Keywords: Financial Literacy; Financial Technology; Risk Tolerance; Investment Interest.